Research and Development of a Transportable Optical Ground Station in NICT: The Results of the First Performance Test - Saito, Yoshihiko; Takenaka, Hideki; Shiratama, Koichi; Munemasa, Yasushi; Carrasco-Casado, Alberto; Trinh, Phuc V.; Suzuki, Kenji; Fuse, Tetsuharu; Takahashi, Yasuhiro; Kubo-oka, Toshihiro; Toyoshima, Morio (Frontiers in Physics, 2021)
In recent years, the necessity of free-space optical (FSO) communications has increased as a method for realizing high-speed communications between satellites and the ground. However, one disadvantage of FSO communications is the significant influence of the atmosphere. Specifically, FSO communications cannot be utilized under certain atmospheric conditions, especially in the presence of clouds. One of the solutions to this problem is the site diversity technique, which makes it possible to select a given ground station with better atmospheric conditions among a number of fixed ground stations. The other solution is to prepare a ground station that can be moved to a place with better atmospheric conditions. We applied the latter method and developed a transportable optical ground station in NICT. We utilize a realistic telescope diameter, which is about 30 cm at the maximum, capable of being set up quickly, and with a pointing accuracy of about 100 µrad. In addition, it is necessary to prepare a fine-pointing optical system that performs tracking with about 1/10 of the pointing accuracy of the telescope. In this paper, we report the results of the first performance test of the transportable optical ground station in NICT.